Evaluation of adverse events and health‐related quality of life in patients with colorectal cancer receiving ambulatory home‐based chemotherapy in Thailand - Suwannee Sirilerttrakul; Noppakan Wannakansophon; Pinyo Utthiya; Sineenuch Ckumdee; Patamaporn Tangteerakoon; Phichai Chansriwong (Wiley, 2021)
Abstract Aims To compare adverse events and health‐related quality of life in ambulatory home‐based chemotherapy with those in inpatient. Design Prospective non‐randomized observational study. Methods Participants were divided into two groups according to patients' preference receiving chemotherapy. Results Sixty‐four participants were enrolled in the inpatient, and 111 were in an ambulatory home‐based chemotherapy. The frequency of anaemia, neutropenia and thrombocytopenia was significantly higher in inpatient group than in ambulatory home‐based chemotherapy group (p < .001, <.001 and .002, respectively). Nausea, mucositis, and fatigue were more common in ambulatory home‐based chemotherapy group than in inpatient group (p < .001, .022, and .005, respectively). Patients in the ambulatory home‐based chemotherapy group showed higher social well‐being (SWB) scores than inpatient group (coefficient 1.92, 95% confidence interval [CI] 0.65 to 3.19, p .003).